2013
DOI: 10.1042/cs20130105
|View full text |Cite|
|
Sign up to set email alerts
|

Relaxin improves multiple markers of wound healing and ameliorates the disturbed healing pattern of genetically diabetic mice

Abstract: Diabetic mice are characterized by a disrupted expression pattern of VEGF (vascular endothelial growth factor), and impaired vasculogenesis during healing. Experimental evidence suggests that RLX (relaxin) can improve several parameters associated with wound healing. Therefore we investigated the effects of porcine-derived RLX in diabetes-related wound-healing defects in genetically diabetic mice. An incisional wound model was produced on the back of female diabetic C57BL/KsJ-m+/+Leptdb (db+/db+) mice and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
5
42
0
Order By: Relevance
“…Our findings are similar to a previous study which reported serelaxin had no effects on blood glucose levels in Type 1 diabetic mice31. However, in a mouse model of Type 2 diabetes, serelaxin reduced blood glucose levels3032. We anticipated a decrease in plasma osmolality in the serelaxin-treated mice because previous studies have shown that shorter durations of serelaxin treatment in rats decreased plasma osmolality33.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar to a previous study which reported serelaxin had no effects on blood glucose levels in Type 1 diabetic mice31. However, in a mouse model of Type 2 diabetes, serelaxin reduced blood glucose levels3032. We anticipated a decrease in plasma osmolality in the serelaxin-treated mice because previous studies have shown that shorter durations of serelaxin treatment in rats decreased plasma osmolality33.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, the normal angiogenic process is delayed and poorly functional. Disturbance of the mechanisms underlying angiogenesis and vasculogenesis, including altered VEGF and expression, has been previously described in db/db animals (Nguyen et al ., ; Bitto et al ., ). The present findings further strengthen these observations, suggesting that reduced inflammation at the wound site improves both angiogenesis and vasculogenesis, improving, in turn, the healing of wounds in the diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are likely important in promotion of wound healing (Bitto et al, 2013) and also in the heavy, irregular, or prolonged menstrual bleeding that accompanies relaxin administration (Unemori et al, 1999). Relaxin also increases arterial compliance by its effects on geometric remodeling (increases in unstressed wall area and wall-to-lumen area ratio) and compositional remodeling (decrease in collagen-to-total protein ratio) in certain arteries (Chan and Cipolla, 2011;Debrah et al, 2011;Gooi et al, 2013).…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 99%
“…In preclinical studies in lean mice that are insulin-resistant after a high-fat diet, relaxin increases glucose uptake into skeletal muscle by improving hemodynamics and angiogenesis that is known to be an important factor in determining the response to insulin (Bonner et al, 2013). More recently, relaxin applied over 12 days in a genetic mouse model of T2DM lowered blood glucose levels, from an average of 660 mg/dl in vehicle-treated animals to 490 mg/dl (Bitto et al, 2013). In addition, relaxin has also been shown to activate peroxisome proliferator-activated receptor-g and enhance the actions of the peroxisome proliferator-activated receptor-g activator rosiglitazone in cells expressing RXFP1 (Singh and Bennett, 2010).…”
mentioning
confidence: 99%